2020
DOI: 10.3389/fsurg.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Acute Limb Ischemia Secondary to Iatrogenic Distal Embolization Using Catheter Directed Aspiration Thrombectomy

Abstract: Objective: Acute limb ischemia (ALI) due to thromboembolism is a limb-and life-threatening condition regularly encountered by vascular surgeons. Iatrogenic distal embolization is occasionally seen as a complication of various endovascular procedures. We present a series of four patients who developed ALI due to arterial embolization during cardiovascular procedures that were successfully treated via catheter directed aspiration embolectomy. Methods: Retrospective review of demographics, risk factors, and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…In this situation, the Penumbra aspiration system (Penumbra Inc., Alameda, California), which has a soft tip to facilitate tracking of tortuous brain vessels and perform large-bore aspiration power for stroke intervention, is most suitable in this scenario. Farhat-Sabet et al reported using Penumbra Indigo (Penumbra Inc., Alameda, California) to successfully treat iatrogenic distal embolization in four patients with acute limb ischemia ( 8 ). In the PRISM trial, the reported success rate with Penumbra Indigo aspiration catheter was 87.2% ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, the Penumbra aspiration system (Penumbra Inc., Alameda, California), which has a soft tip to facilitate tracking of tortuous brain vessels and perform large-bore aspiration power for stroke intervention, is most suitable in this scenario. Farhat-Sabet et al reported using Penumbra Indigo (Penumbra Inc., Alameda, California) to successfully treat iatrogenic distal embolization in four patients with acute limb ischemia ( 8 ). In the PRISM trial, the reported success rate with Penumbra Indigo aspiration catheter was 87.2% ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Commercial suction thrombectomy devices, such as the Penumbra Indigo System (Penumbra, Alameda, CA, USA), are also available and effective. 13,15 However, these devices are expensive and cumbersome to set up in a clinically emergent situation. Also, they require the use of a larger catheter than that required for the EPD technique, carrying the risk of emboli dislodgement distally.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous minimally invasive treatment options have been described, but none is established as the “gold standard,” nor are they effective in all circumstances. 1115…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages with the Angiovac apparatus include the large cannula size, hemodynamic perturbations from blood loss, need for an extracorporeal circulation and risk of right heart perforation due to due to the device's limited maneuverability. 30,31 C. Penumbra Indigo System (Penumbra Inc., Alameda, California): 32,33 The Penumbra system is a suction aspirator device that has a proprietary "smart" catheter tubing system that can adjust the suction applied across the catheter to establish suction. Sista et al evaluated the Penumbra system in a multi-center single-arm study that enrolled 119 acute submassive PE patients in the EXTRACT-PE study.…”
Section: Acute Interventional Pe Therapy: Mechanical Thrombectomy and Embolectomymentioning
confidence: 99%